SUSPECTED LEFT ADRENOCORTICAL CARCINOMA LATER DIAGNOSED AS EXTRA-ADRENAL COMBINED SCHWANNOMA AND GANGLIONEUROMA - Azman, Siti Sanaa Wan; Ali, Masliza Hanuni Mohd; Li, Cheng Mao; Mohamed, Hussain; Muda, Nor Hisham; Wahab, Wan Nor Najmiyah Wan Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Ganglioneuromas and schwannomas are both rare benign tumours. They arise from different types of nerve cells: ganglioneuromas from autonomic ganglion cells and schwannomas from nerve sheath cells (Schwann cells). A combined adrenal ganglioneuroma and schwannoma is extremely rare, representing 1.4% of adrenal incidentalomas. CASE We present a 41-year-old male with an underlying left ureteric calculus who was referred for left adrenal incidentaloma from CT urography (CTU). He had no history of paroxysms of headache, sweating or palpitations. There were no symptoms to suggest Cushing's or underlying malignancy. On examination, he was normotensive and there were no discriminatory features of Cushing's. Laboratory evaluation showed normal potassium (4.3 mmol/L), and the overnight dexamethasone test (ODST) was appropriately suppressed (12 nmol/L). 24-hour urine metanephrine was within normal range. Testosterone and DHEAS were within the normal range with 19 nmol/L and 3.830 umol/L levels, respectively. Initial CTU reported a left adrenal mass measuring 4.0 x 3.1 x 3.8 cm. The adrenal CT demonstrated a left adrenal mass measuring 4.1 x 3.2 x 4.0 cm, with a 39 Hounsfield unit, an absolute washout of 28% and a relative washout of 16%. These findings indicate an indeterminate adrenal mass with a differential of adrenocortical carcinoma or pheochromocytoma. He underwent a left adrenalectomy and was discharged well. Histopathological examination showed an encapsulated biphasic tumour. There were Verocay bodies, and the neoplastic cells were narrow, elongated and wavy with tapered ends, interspersed with collagen fibres, which are distinct characteristics of schwannomas. At the periphery of the tumour, a separate proliferation of spindle cells with multiple ganglion cells was seen, indicative of ganglioneuromas. Sections of the adrenal gland show an uninvolved cortex and medulla. CONCLUSION In our case, ganglioneuromas may have arisen from the paravertebral sympathetic plexus located retroperitoneally. This rare condition may mimic adrenal malignancy radiologically, and the modality of treatment is surgical excision.